The illustrated directory of uniforms, weapons, and equipment of the civil war - Miller, David (David M.O.) (Salamander Books Limited, 2001)
This wide-ranging display of artifacts from the Civil War will be an essential reference for collectors of military paraphernalia, wargamers, and anyone interested in military history. Weapons and uniforms of both the North and South have been photographed in vivid color for this book. Experts at West Point Military Academy and other military history establishments approved the carefully researched and specially commissioned artwork of uniformed figures that appear in this directory. Find superb photos of rifles, muskets, and handguns, ammunition, swords, bayonets, artillery pieces and shells, as well as badges of rank, medals, belt buckles and uniforms.